Welfare through Work : Conservative Ideas, Partisan Dynamics, and Social Protection in Japan - Miura, Mari (Book collections on Project MUSE., 2012)
"This book argues that the Japanese social protection system should be understood as a system of "welfare through work," where employment protection has functionally substituted for income maintenance"--Publisher's Web site.